The impact of inflation targeting on unemployment in developing and emerging economies - Jose Angelo Divino (International Policy Centre for Inclusive Growth (IPC-IG), 2009)
Several countries around the world have adopted the inflation targeting regime for monetary policy. Despite the growing literature on the issue, it is not clear whether developing and emerging countries can improve their economic performance by adopting inflation targeting. This working paper examines the extent to which macroeconomic policies anchored to inflation targeting affect unemployment, economic growth and the output gap. The results show that inflation targeting causes no harm to employment in developing and emerging countries. On the contrary, it might reduce average unemployment and narrow the output gap. Given that the change in regime must be accompanied by institutional and economic reforms to fiscal and exchange rate policies, targeters might be better off than non-targeters. Hence there is no apparent reason to condemn the adoption of the inflation targeting regime by developing and emerging countries.
Keywords: 330; Inflation targeting; Unemployment; Economic growth; Output gap; Inflation Targeting; Arbeitslosigkeit; Wirtschaftswachstum; Gesamtwirtschaftliche Produktion; Entwicklungsländer; Schwellenländer